Mixing of Photons with Light Pseudoscalars in Time-Dependent Magnetic Fields - Gamboa-Rios, J; Arias-Reyes, P (Springer New York LLC, 2016)
The effects of an external time-dependent magnetic field in the conversion probability of photon- to axion-like particles are studied. Our findings show that for a certain time regime, the amplitude of the produced axion-like field can be enlarged with respect to the static case, thus enhancing the probability of conversion. © 2016, The Author(s).